Nowe wykorzystanie blogów internetowych. Ewolucja w stronę funkcji dydaktycznej - Polcyn-Matuszewska,, Sylwia Maria (Kultura-Społeczeństwo-Edukacja, 2014)
Nowadays blogs have been acquiring new functions. Apart from traditional blogs, one can see a growing number of blogs that have a didactic function. Blogs have been used more and more often by the teachers at different education levels in order to support and optimise the teaching and learning processes. Linking entertainment and teaching, they have become a place of unlimited possibilities for the students, where students can acquire new knowledge, develop their own interests and increase cognitive curiosity. Educational blogs that are used actively by the teachers can positively influence educational process and introduce students to self-education, thus preparing them to the process of lifelong learning in the future.